Digital Surveillance and the Right to Privacy: Legal Challenges of State Authority in the Era of Big Data Governance - Awais Syafik; Muslim Muslim; Imroatun Solekah (International Journal of Law and Political Authority, 2026)
This study examines the legal challenges arising from digital surveillance practices and the protection of privacy rights within the expanding framework of big data governance. The research employs an empirical legal approach grounded in normative analysis through examination of statutory regulations, judicial decisions, and institutional monitoring reports concerning state surveillance authority, personal data protection, and digital governance practices. Primary legal materials consist of Indonesian personal data protection and electronic information regulations, while secondary sources include comparative legal scholarship, privacy doctrine, surveillance theory, and reports issued by privacy watchdog institutions. The findings demonstrate that contemporary surveillance governance increasingly operates through algorithmic systems, biometric monitoring, predictive analytics, and automated decision making infrastructures that extend beyond conventional legal safeguards regulating personal data processing. Existing legal frameworks provide formal recognition of privacy rights and data protection obligations, yet institutional implementation remains constrained by weak oversight mechanisms, fragmented accountability structures, and limited regulation of artificial intelligence based surveillance systems. The study argues that future constitutional protection requires regulatory reconstruction integrating algorithmic accountability, collective privacy protection, independent supervisory institutions, and adaptive governance principles capable of limiting disproportionate exercises of digital state authority.